Event-related potentials to rare visual targets and negative symptom severity in a transdiagnostic psychiatric sample. Issue 7 (July 2021) - Salgari, Giulia C.; Potts, Geoffrey F.; Schmidt, Joseph; Chan, Chi C.; Spencer, Christopher C.; Bedwell, Jeffrey S.
Highlights: P3b and N2b mean amplitudes were inversely related to the Positive and Negative Syndrome Scale – Negative Symptom Factor severity score across a transdiagnostic psychiatric sample. A significant negative transdiagnostic relationship was found between P3b mean amplitude and blunted affect severity. This suggests that people with a greater severity of blunted affect may not allocate sufficient cognitive resources engaging in activities requiring selective attention. Abstract: Objectives: Negative psychiatric symptoms are often resistant to treatments, regardless of the disorder in which they appear. One model for a cause of negative symptoms is impairment in higher-order cognition. The current study examined how particular bottom-up and top-down mechanisms of selective attention relate to severity of negative symptoms across a transdiagnostic psychiatric sample. Methods: The sample consisted of 130 participants: 25 schizophrenia-spectrum disorders, 26 bipolar disorders, 18 unipolar depression, and 61 nonpsychiatric controls. The relationships between attentional event-related potentials following rare visual targets (i.e., N1, N2b, P2a, and P3b) and severity of the negative symptom domains of anhedonia, avolition, and blunted affect were evaluated using frequentist and Bayesian analyses. Results: P3b and N2b mean amplitudes were inversely related to the Positive and Negative Syndrome Scale-Negative Symptom Factor severity score across the entire sample. Subsequent regression analyses showed a significant negative transdiagnostic relationship between P3b amplitude and blunted affect severity. Conclusions: Results indicate that negative symptoms, and particularly blunted affect, may have a stronger association with deficits in top-down mechanisms of selective attention. Significance: This suggests that people with greater severity of blunted affect, independent of diagnosis, do not allocate sufficient cognitive resources when engaging in activities requiring selective attention.